Analisis Vertical Plate pada Variasi Aliran di Lunas SPAR - Rati Ahmad (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2023)
The progress of human civilization today is also followed by increasing demand to fulfill energy needs, including the need for oil and gas. SPAR (Single Point Anchor Reservoir) is one of the suitable and efficient offshore floating structures for use in deep waters for drilling, production, processing, storage and as a renewable power plant. SPAR Platform consists of a cylinder that floats vertically in the water. The natural period of SPAR structures spread across the Gulf of Mexico generally has a natural period of 60 s for pitch. Vertical Plate can be an alternative solution to reduce rotational movement so that the SPAR system becomes more stable and functions more efficiently. The research method conducted in this study is a numerical calculation method using the application of computational fluids dynamics (CFD). The most turbulence flow occurs at a speed variation of 0.1 m/s, so it is concluded that not always the greatest flow velocity that passes through the vertical plate will also occur a lot of turbulence flow. Simulating the flow speed after passing through the vertical plate will become turbulence flow and the speed decreases due to the flow become turbulence. The speed change that occurs in simualation with 3 speed variations of 0.1 m/s, 1 m/s, and 10m/s exceeds the same speed change ratio of 1.52. The greatest pressure occurs in simulations on the vertical plate that is directly exposed to the direction in which the flow comes.